ANALISIS PERMINTAAN AGREGAT DAN PENAWARAN AGREGAT - Fatkhu Rohman; Lailatul Fitriah; Santo Ardiyanto; Bagus Eka Narendra S; Sarpini E.S (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to conduct empirical and theoretical analysis of aggregate supply and demand. Relevant data was collected using a literature review and qualitative methodology. This research identifies the variables that influence overall supply and demand. Research findings show that although increasing aggregate demand can spur job creation and economic expansion, it can also lead to inflation. On the other hand, increasing total supply can increase output and stabilize prices. Based on a case study conducted in Indonesia, household spending is the main driver of growth in aggregate supply and demand between 2021 and 2023. Policymakers can benefit from this research's broader understanding of macroeconomic dynamics and capabilities to help them make economic plans successful one